Rootstocks for almond. Present situation - Felipe A.J. (Séminaire du GREMPA sur les portes-greffes de l'amandier, 1989)
Almond growing has undergone essential changes in the Mediterranean countries during the last years. Newly released cultivars, late blooming and self-compatible, already represent a good advance in production. There are also good possibilities to reach a similar advance by the use of new selected rootstocks, both seedling (peach and almond) and clonal (plums and hybrids). Especially interesting is the selection of new interspecific plum hybrids, which may broaden the adaptation of almond growing to different soil conditions and incorporate resistance to different pests and diseases related to the soil. Some work is already advancing in this way and a wide range of new rootstocks are under study.
Séminaire du GREMPA sur les portes-greffes de l'amandier, 1988/11/29-30, Saragoza (Spain)